The Effect of Digital Content Marketing on Tourists’ Purchase Intention - Serife Yazgan Pektas; Azize Hassan (Journal of Tourismology, 2020)
The purpose of this study is to reveal the effect of digital contents on tourists’ purchase intention using the persuasion knowledge model. For this purpose, data were collected by purpose sampling method between 25 December 2018 and 31 January 2019 with the approval of Bartin University Social and Humanities Ethics Committee. The obtained 105 data were analyzed. As a result of the analysis, it was found that there were significant positive relationships between tourists’ purchase intention, eWOM and suspicion sub-dimensions (reliability, disbelief). While the reliability of the subdimensions of the suspicion scale influenced eWOM and tourists’ purchase intention, it did not appear to have an impact on persuasive information. In addition to the negative correlation between persuasion and suspicion sub-dimensions, it was found that the sub-dimensions of suspicion did not affect persuasion.